Strengthening health care to provide rehabilitation services for women with cancer diseases of the reproductive system - D. V. Blinov; A. G. Solopova; A. N. Plutnitskiy; D. M. Ampilogova; L. N. Sandzhieva; D. I. Korabel’nikov; D. A. Petrenko (Фармакоэкономика)
During the past decades, the prevalence of cancer diseases of female reproductive system has been constantly growing. The issue is especially acute in reproductive-age women because of earlier oncological pathology onset. Morpho-functional disorders and aggressive methods of anti-tumor therapy significantly affect the patients’ quality of life, psychological well-being, emotional stability, and family relationship, which leads to a limitation of physiological and social possibilities. Rehabilitation programs for oncological patients target to prevent unwanted sequela of the disease, its therapy, and relapses. Pre-rehabilitation plays a special role. It includes psychological and specialized medical care for the patient during the period from the disease verification to the start of therapy. Timely rehabilitation measures reduce the rate of repeated hospitalizations for side effects of chemotherapy, radiotherapy complications, antitumor therapy, and radical surgical interventions. Rehabilitation as a part of standard therapeutic strategy can reduce pharmacoeconomical burden for the health care system. However, further clinical and pharmacoeconomic studies are required for the implementation of rehabilitation at the level of the health care system.